Remote Microphone Hearing Aid Use Improves Classroom Listening, Without Adverse Effects on Spatial Listening and Attention Skills, in Children With Auditory Processing Disorder: A Randomised Controlled Trial - Stavrinos, Georgios; Iliadou, Vasiliki (Vivian); Pavlou, Menelaos; Bamiou, Doris-Eva (Frontiers in Neuroscience, 2020)
Background: Children with Auditory Processing Disorder (APD) often have poor auditory processing skills in the presence of normal peripheral hearing. These children have worse listening-in-noise skills compared to typically developing peers, while other commonly reported symptoms include poor attention and distractibility. One of the management strategies for children with APD is the use of Remote Microphone Hearing Aids (RMHAs), which can help improve the signal-to-noise ratio in the child’s ears. The aim of this randomised controlled trial was to examine whether RMHAs improved classroom listening in children with APD, and to further test their effects on children’s listening-in-noise and attention skills following a 6-month intervention. Methods: Twenty-six children diagnosed with APD, aged 7-12, in primary mainstream education, were randomised into the intervention (N = 13) and control group (N = 13). The primary outcome measure was the Listening Inventory for Education – Revised questionnaire, completed by children to assess their listening using RMHAs under several acoustically challenging situations in the classroom. Secondary outcome measures included the Listening in Spatialised Noise – Sentences test, assessing speech-in-noise perception and spatial listening, and the Test of Everyday Attention for Children, assessing different types of attention skills. Tests were conducted in unaided conditions. Mixed analysis of variance was used to analyse the data. The clinical trial was registered at clinicaltrials.gov (unique identifier: NCT02353091). Results: The questionnaire scores of self-reported listening skills in the classroom significantly improved in the intervention group after 3, MD = 7.31, SE = 2.113, p = .014, and after 6 months, M = 5.00, SE = 1.468, p = .016. The behavioural measures of listening-in-noise and attention did not significantly change. Conclusion: Use of RMHAs improves classroom listening, evidenced by the results of the questionnaire analysis, while a 6-month use did not have adverse effects on unaided spatial listening or attention skills.